Reduced platelet aggregation after fluvastatin therapy is associated with altered platelet lipid composition and drug binding to the platelets - Osamah, Hussein (1997)
Aims High plasma cholesterol concentration and increased platelet activity are two major risk factors for atherosclerosis. Lovastatin, the lipophilic drug was shown to inhibit platelet aggregation whereas pravastatin, the hydrophilic drug had no such effect. Analysis of the effect of fluvastatin which is both a lipophilic and hydrophilic drug, on platelet aggregation was the goal of the present study. Methods Fluvastatin 40 mg daily was administered to 25 patients with hypercholesterolaemia for up to 24 weeks. Normal subjects acted as controls. The influence of fluvastatin on plasma lipids and on platelet aggregation and fluidity was studied. The direct effect of fluvastatin on platelets was compared with that of other statins. Results Fluvastatin therapy (40 mg day(−1) for a period of 4 weeks) in hypercholesterolaemic patients resulted in a 23% and 29% reduction in plasma levels of total cholesterol and LDL-cholesterol respectively. Platelet cholesterol/phospholipids molar ratio was reduced by 26% and platelet aggregation was significantly (P<0.02) reduced by 10% after 4 weeks of fluvastatin treatment. On continuing fluvastatin therapy for additional 20 weeks, no further decrement in plasma LDL cholesterol levels or in platelet cholesterol/phospholipid ratio were noted. However, platelet aggregation was further significantly (P<0.01) reduced by up to 15%. Incubation of platelets with increasing concentrations of fluvastatin or lovastatin, demonstrated a dose-dependent reduction in platelet aggregation, whereas pravastatin showed no effect. This inhibitory effect of fluvastatin or lovastatin on platelet aggregation (up to 34% or 22% respectively at a concentration of 1 μg statin ml(−1) ) was found both in platelet rich plasma and in washed platelet suspensions. Fluvastatin and lovastatin (but not pravastatin), seem to share similar platelet binding sites, as non labelled fluvastatin or lovastatin were able to displace []> (3)H]-labeled-fluvastatin from its binding sites on platelets. Conclusions Fluvastatin therapy reduces platelet aggregation via a dual effect which involves its in vivo hypocholesterolaemic action on platelet cholesterol content, and also a direct effect of the drug binding to the platelets. The antiatherogenicity of fluvastatin may be related, in addition to its plasma cholesterol lowering ability, to its inhibitory effect on platelet activation.